Investigation of white LEDs based MIMO visible light communication system - Kwek, Han Cong (2017)
As we progress forward into the future, we have pushed certain systems to their limit. Therefore, with regards to wireless communication we need to try different methods to ensure that we keep innovating at a fast pace. Multiple input and multiple output (MIMO) system used for wireless communication can greatly increase the spectral efficiency given the transmission power used. MIMO systems use different multipaths to propagate the transmission signal. By making use of the multipath transmission, we can solve many problems associated with the traditional system which uses single input and single output (SISO) system. However, this have resulted in new problems as it causes the algorithms to become more complex. Furthermore, using multiple antennas at the same time will create inter-channel interference. Therefore, we need to find the method of MIMO transmission which have minimum inter-channel interference. Simulations of spatial multiplexing and spatial modulation will be conducted and the simulation data recorded. Advantages and disadvantages of spatial multiplexing and spatial modulation will also be discussed.